Brachial plexus neuropathy or neuritis in the dog and cat: A report of 4 spontaneous cases - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; POLIZOPOULOU (Ζ.Σ. .ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S.; GEORGIADIS (Γ. ΓΕΩΡΓΙΑΔΗΣ), G.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ), M. (Journal of the Hellenic Veterinary Medical Society, 2018)
One kitten and three adult dogs were admitted with a history of an acute or progressive lower motor neuron disease involving asymmetrically the thoracic limbs. Neurogenic muscular atrophy was also present affecting the relevant muscles in all the animals. As no other neuromuscular abnormalities could be detected on physical, radiological and clinicopathologic examination, a tentative diagnosis of brachial plexus neuropathy or neuritis was made. In the cat diagnosis was confirmed by electrophysiological testing demonstrating decreased sensory conduction velocity of the ulnar nerve and denervation potentials. The administration of prednisolone at antiinflammatory dosage for 3 weeks abolished or decreased the severity of the clinical signs in all the cases. Recurrence of the disease, one to 6 months after the cessation of treatment, was detected or reported for the 3 dogs where a follow-up was possible.